2009
DOI: 10.1134/s1022795409110118
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome synteny of the a genome of two evolutionary wheat lines

Abstract: In order to estimate synteny between A(t) and A polyploid wheat genomes belonging to different evolutionary lines (Timopheevi and Emmer), saturation of chromosome maps of Triticum timopheevii A(t) genome by molecular markers has been conducted. Totally, 179 EST-SSR and 48 genomic SSR-markers have been used with the following integration of 13 and 7 markers correspondingly into chromosome maps of A(t) genome. ESTSSR showed higher transferability and lower polymorphism than genomic SSR markers. The chromosome ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…This method is particularly important for the genetic analysis of alien chromatin from wheat relatives that lack specifically developed DNA markers (Dobrovolskaya et al, 2009). Because genomes A and B from octoploid Tritileymus should match well with genomes A and B of durum wheat, these should be inherited stably in hybrids of octoploid Tritileymus M842-16 x Triticum durum D4286, and substitutions are instead most likely to occur between genomes D and Ns from octoploid Tritileymus.…”
Section: Discussionmentioning
confidence: 99%
“…This method is particularly important for the genetic analysis of alien chromatin from wheat relatives that lack specifically developed DNA markers (Dobrovolskaya et al, 2009). Because genomes A and B from octoploid Tritileymus should match well with genomes A and B of durum wheat, these should be inherited stably in hybrids of octoploid Tritileymus M842-16 x Triticum durum D4286, and substitutions are instead most likely to occur between genomes D and Ns from octoploid Tritileymus.…”
Section: Discussionmentioning
confidence: 99%
“…No 4A t L.7GS translocation has been found in timopheevii wheats. As an alternative, a distal 4A t L.3A t L translocation was identified, resulting in the absence of collinearity between the distal regions of chromosomes 4AL and 4A t L (Jiang and Gill 1994b;Maestra and Naranjo 1999;Rodriguez et al 2000;Salina et al 2006;Dobrovolskaya et al 2009). There is no evidence of the presence or absence of inversions on chromosome 4A t .…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the localization of a homeologous minor QTL for powdery mildew in a collinear region of chromosome arm 7AS in the line 8.1. However, the published T. militinae (T. timopheevii) maps do not cover the distal part of chromosome arm 7GS (Salina et al 2006;Dobrovolskaya et al 2009) and no additional markers specific for the QPm.tut-4A region are available. Thus, the exact origin of the 4A introgression cannot be resolved at present.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with unexpressed sequence markers (e.g. SSR), these markers are highly conserved and particularly effective and accurate for determining the homologous relationships of alien chromosomes in wheat background (Dobrovolskaya et al 2009). Du et al (2013a and b) successfully identified alien chromosomes in two wheat-P. huashanica addition lines, 59-11 and 3-8-10-2, which were designated as 6Ns and 5NS based on EST-SSR and EST-STS marker analysis, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In wheat-related species such as Th. ponticum, where there is a lack of molecular biology information, the transfer of wheat molecular markers to the species is a feasible method for genetic analysis (Dobrovolskaya et al 2009). Over the last two decades, SSR markers have been used extensively as a effective tool for the genetic analysis of alien chromosomes in various species, such as Thinopyrum ponticum (Hu et al 2011), Thinopyrum intermedium (Lin et al 2007), Triticum timopheevii (Uhrin et al 2012), Leymus mollis (Zhao et al 2013) and Secale cereale (Tang et al 2008).…”
Section: Discussionmentioning
confidence: 99%